Peningkatakan Aktivitas dan Hasil Belajar Siswa Pendidikan Agama Katolik Melalui Model Project Based Learning Pada Fase F di SMK Negeri 2 Palangka Raya - Morita Bayudita Eliananda (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2023)
The purpose of this study was to improve the activities and learning outcomes of Catholic religious education and ethics students on the material of developing a culture of love, so that they can act correctly and appropriately through the Project Based Learning learning model. This research is a classroom action research involving 16 Catholic students of Phase F of SMK Negeri 2 Palangka Raya in the 2023/2024 academic year. The action was carried out in two learning cycles. Data were collected using observation guidelines, tests in each cycle, and analyzed descriptively qualitatively. The results showed that in cycle I the average percentage of student learning activities was 69.53% with classical completeness of cognitive learning outcomes obtained at 68.75%, with an average learning outcome score of 76.31. In cycle II, the average percentage of student learning activities was 93.75% with classical completeness of cognitive learning outcomes of 93.67%, with an average learning outcome value of 86.43. Thus, the application of the use of the Project Based Learning learning model with the help of Canva TTS can improve student learning activities and outcomes.